Impact of 1,2-ethanedithiol treatment on luminescence and charge-transport characteristics in colloidal quantum-dot LEDs - Nguyen, Huu Tuan; Ryu, Shin Young; Duong, Anh Tuan; Lee, Soonil (Nanotechnology, 2019)
We report on a substantial increase in luminance and luminous efficiency of green-light emitting devices (LEDs) that use colloidal CdSe@ZnS quantum dots (QDs) as a light-emitting material in response to treatment with 1,2-ethanedithiol (EDT). The maximum luminance increased from 1146 to 8075 cd m-2, and luminous yield from 0.15 to 1.41 cd A-1 as a result of treating an incomplete device with drops of EDT right after spin-coating QDs onto a ZnO-nanoparticle layer. Based on systematic studies on substrate-dependent change in photoluminescence, and current-voltage and luminance-voltage characteristics, we propose that passivation of intra-gap defect states and relative shifts of energy levels relevant to the operation of QD LEDs are two main results of EDT treatment. In particular, we argue that energy-level shift without emission-color change can be attributed to surface-dipole effects.
Keywords: 1,2-ethanedithiol (EDT) treatment; CdSe-ZnS; Colloidal quantum dots; Defect state; Light emitting materials; Luminance voltage characteristics; Surface dipole; Transport characteristics; 1,2-ethanedithiol (EDT) treatment; defect-state passivation; green-emitting CdSe@ZnS; quantum-dot LED; surface-dipole effect